Effect of quantum dot shape of the GaAs/AlAs heterostructure on interlevel hole light absorption - Boichuk, V.I.; Bilynskyi, I.V.; Sokolnyk, O.A.; Shakleina, I.O. (Condensed Matter Physics, 2013)
The effect of quantum dot shape on the hole energy spectrum and optical properties caused by the interlevel charge transition based on the 4x4 Hamiltonian has been studied for the GaAs quantum dot in the AlAs semiconductor matrix. Calculations have been carried out in perturbation theory taking into account the hybridization of states for cubic, ellipsoidal, cylindrical and tetrahedral shapes by changing the volume of a quantum dot. Based on the energy calculations and on the determined wave functions of the hole states we have defined the selection rules and the dependence of the interlevel hole absorption coefficient on QD shapes and volumes. Для квантової точки GaAs у напiвпровiдниковiй матрицi AlAs дослiджено вплив форми квантової точки на енергетичний спектр дiрки та оптичнi властивостi, зумовленi мiжрiвневими переходами заряду, на основi гамiльтонiана 4×4. Обчислення проводились за допомогою теорiї збурень з врахуванням гiбридизацiї станiв для кубiчної, елiпсоїдальної, цилiндричної та тетраедричної форми при змiнi об’єму квантової точки. На основi проведених обчислень енергiї та визначених хвильових функцiй станiв дiрки встановлено правила вiдбору та дослiджено залежнiсть коефiцiєнту мiжрiвневого дiркового поглинання свiтла вiд форми та об’єму квантової точки.